Possible contribution of rare alleles of human ACE2 in the emergence of SARS-CoV-2 variants escaping the immune response - Devaux, Christian A.; Fantini, Jacques (Frontiers in Immunology, 2023)
Since the start of the SARS-CoV-2 pandemic, the rapid replacement of one lineage by another has been observed. Indeed, SARS-CoV-2 is evolving through a quasispecies mechanism leading to post-infection mutation selection under positive evolutionary pressure (host-driven viral evolution). These mutations may reduce the effectiveness of the specific neutralizing immune response against the virus. We provide here evidence that apart from the selection of SARS-CoV-2 variants by the immune system, selection by the cellular receptor can just as well select variants which escape neutralization.